Physical attributes of Humic Cambisol subjected to nitrogen sources in an apple orchard - Schmitz, Daniela; Loss, Arcângelo; Lourenzi, Cledimar Rogério; Müller Júnior, Vilmar; Veiga, Milton da; Brunetto, Gustavo; Comin, Jucinei José (Comunicata Scientiae, 2018)
The application of nitrogen sources in soil under apple orchards can change the soil physical attributes and soil-plant relationship. The objective was to evaluate the physical attributes of Humic Cambisol (Inceptisol) in an apple orchard, under nitrogen sources in Urubici county, Santa Carina State, Brazil. The treatments were: control (without fertilization), common urea, pelleted urea and organic fertilizer (pig deep-litter), at rates of 33 kg N ha-1 yr-1. After two years of implementation of the N sources, soil undisturbed samples were collected at layers of 0.0-0.05, 0.05-0.10, 0.10-0.15 and 0.15-0.20 m depth, and these were evaluated the bulk density (BD); penetration resistance (PR); total porosity, macro, meso, and micropores; the geometric mean diameter of air-dried aggregates (GMDad) and water-stable aggregates (GMDws) and water content. The organic fertilizer increased the total porosity, microporosity, the water content and decreased BD, compared to other treatments, at the layer of 0.0-0.05 m depth. The organic fertilization and the common urea did not change the macroporosity and PR, but provided lower macroporosity, compared to the control, and RP in relation to pelleted urea. The N sources increased GMDws compared with the control in the topsoil.